2012
DOI: 10.1155/2012/630468
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo Cardiomyopathy as a Delayed Complication with a Herbicide Containing Glufosinate Ammonium in a Suicide Attempt: A Case Report

Abstract: Background. Glufosinate ammonium has a famous delayed complication as respiratory failure, however, delayed cardiogenic complication is not well known. Objectives. The aim of this study is to report a takotsubo cardiomyopathy as a delayed complication of glufosinate ammonium for suicide attempt. Case Report. A 75-year-old woman ingested about 90 mL of Basta, herbicide for suicide attempt at arousal during sleep. She came to our hospital at twelve hours after ingesting. She was admitted to our hospital for fear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…A majority of this class of herbicides contain an anionic surfactant that increases blood permeability, resulting in decreasing circulatory blood volume, cardiac function, and resistance of systemic peripheral vessels 20 , 21 . One case report showed that Takotsubo cardiomyopathy was a delayed complication with a herbicide containing glufosinate ammonium in a suicide attempt 7 . Surfactant volume might be an important factor in patients with surfactant-containing herbicide poisoning 21 23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A majority of this class of herbicides contain an anionic surfactant that increases blood permeability, resulting in decreasing circulatory blood volume, cardiac function, and resistance of systemic peripheral vessels 20 , 21 . One case report showed that Takotsubo cardiomyopathy was a delayed complication with a herbicide containing glufosinate ammonium in a suicide attempt 7 . Surfactant volume might be an important factor in patients with surfactant-containing herbicide poisoning 21 23 .…”
Section: Discussionmentioning
confidence: 99%
“…A cardiogenic event generally occurs as a result of the direct effects of poisons on contractility or inotropy of the heart. However, some reports have shown that takotsubo cardiomyopathy, also known as transient left ventricular ballooning syndrome or stress cardiomyopathy, could be one of the causes of cardiac complication in patients with acute poisoning 4 7 . Takotsubo cardiomyopathy is characterized by transient, reversible ventricular dysfunction with normal coronary arteries 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, no systematic study has evaluated the frequency and mechanisms in this setting. We report TTC described in the literature after poisoning with non direct sympathomimetic substances in table 2 [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Tominaga et al previously reported a Takotsubo cardiomyopathy case complicating the contact with a herbicide containing glufosinate ammonium in a suicide attempt [8]. In other cases, apical ballooning was caused by phenylephrine inhaled for relieving nasal congestion [9].…”
mentioning
confidence: 99%